Genomic diversity at the Glu-D1 locus in Aegilops tauschii reveals the origin of elite high-molecular-weight glutenin genes in bread wheat (Triticum aestivum) - Xu, Wanxin; Geng, Shuaifeng; Liu, Shaoshuai; González-Muñoz, Andrea; Liu, Yifan; Deng, Zhongyin; Che, Yuqing; Cui, Dada; Zou, Xinyu; Ziying, Wang; Wang, Xiang; Wang, Daowen; et al. (Elsevier, 2025)
The Glu-D1 locus of the Aegilops tauschii genome carries two high-molecular-weight glutenin genes, Dx and Dy, that are essential for viscoelastic properties of bread wheat dough, contributing to its success as a global staple crop. Here, we examined 48 Ae. tauschii high-quality genome assembles and identified a large dataset of Glu-D1, a locus that has remained recalcitrant to high-resolution analysis due to its genomic complexity. Phylogenetic analysis supported six major clades, slightly differing from the geography-based classification. Despite a short genomic distance, gene-based haplotype analysis detected possible ancestral recombination between Dx and Dy genes that were separated by distinctive repetitive sequences. Biochemically, glutenins of the same length can vary in isoelectric points, causing deviations in migration on traditional SDS-PAGE gels. Differential selection pressures were detected among clades and between Dx and Dy glutenin genes. Two clades, L2E-1 and L2W-2, with relatively lower coeliac motifs, were identified as the most probable ancestral contributors to bread wheat. Furthermore, key amino acids were identified as conceptually suitable for single-base editing to create novel elite alleles. Dissecting genomic diversity of the Glu-D1 loci deepens our understanding of the evolutionary trajectory of these long-studied seed storage proteins and offers new strategies for wheat grain-quality improvement.